High temperature surface neutralization process with random copolymers for block copolymer self‐assembly. Issue 3 (14th November 2016) - Sparnacci, Katia; Antonioli, Diego; Perego, Michele; Giammaria, Tommaso Jacopo; Seguini, Gabriele; Ferrarese Lupi, Federico; Zuccheri, Giampaolo; Gianotti, Valentina; Laus, Michele
Abstract : Hydroxyl terminated poly(styrene‐ r ‐methyl methacrylate) (P(S‐ r ‐MMA)) random copolymers (RCPs), with molecular weight ( M n ) spanning from 1700 to 69 000 g mol −1 and equal styrene unit content, were grafted at different temperatures onto a silicon oxide surface and subsequently used to study the orientation of nanodomains with respect to the substrate, in cylinder forming polystyrene‐ b ‐poly(methyl methacrylate) (PS‐ b ‐PMMA) block copolymer thin films. When the grafting temperature increases from 250 to 310 °C, a substantial increase in the grafting rate is observed. In addition, an increase in the surface neutralization efficiency occurs thus resulting in an increase in the robustness of the surface neutralization step. These data revealed that the neutralization of the substrate is the result of a complex interplay between RCP film characteristics and underlying substrate properties that can be finely tuned by properly adjusting the temperature of the grafting process. © 2016 Society of Chemical Industry Abstract : Hydroxyl terminated P(S‐r‐MMA) random copolymers with different molecular weights were grafted onto a silicon surface by high temperature short time thermal treatments. An increase in the surface neutralization efficiency occurs increasing the grafting temperature from 250 to 310 °C.